Peculiarities of Formation and Melting of Cluster Phase in Highly Concentrated Cryoprotectant Solutions - Sevastianov, Stanislav S.; Osetsky, Aleksandr I. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 188